Mrs. jeffries and the feast of st. stephen eaudiobook - Brightwell, Emily (Mrs. Jeffries, 2019)
She keeps house for Inspector Witherspoon . . . and keeps him on his toes. Everyone's awed by his Scotland Yard successes—but they don't know about his secret weapon. No matter how messy the murder or how dirty the deed, Mrs. Jeffries's polished detection skills are up to the task . . . proving that behind every great man there's a woman—and that a crimesolver's work is never done. A Yuletide dinner in West Brompton should have been a festive occasion, until the host, wealthy Stephen Whitfield, dropped dead before the second course. Now Mrs. Jeffries and the busy sleuths must rally in support of their Inspector, especially since the clues are harder to find than a silver sixpence in a plum pudding.